2021
DOI: 10.21203/rs.3.rs-180980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-fatal Senior Pickleball and Tennis-related Injuries Treated in United States Emergency Departments, 2010-2019

Abstract: Background: Pickleball is growing rapidly with a passionate senior following. Understanding and comparing players’ injury experience through analysis of a nationally representative hospital emergency department sample helps inform senior injury prevention and fitness goals.Methods: A retrospective population-based cohort study was performed using 2010 to 2019 data from the U.S. Consumer Product Safety Commission’s (CPSC) National Electronic Injury Surveillance System (NEISS). Non-fatal pickleball and tennis-re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…The most common mechanism of injury was classified as a slip, trip, fall, or dive comprising just over 63% of cases. Similar to the analysis from Forrester et al (15), strains or sprains were the most common injuries reported (33.2%); fractures were the second most common pickleball injury (28.1%) reported (35). However, in the analysis by Weiss, upper-body injuries, such as to the wrist, were slightly more common than lower-body injuries (13.2%, 12.9%) (35).…”
Section: Pickleball Needs Analysissupporting
confidence: 61%
See 3 more Smart Citations
“…The most common mechanism of injury was classified as a slip, trip, fall, or dive comprising just over 63% of cases. Similar to the analysis from Forrester et al (15), strains or sprains were the most common injuries reported (33.2%); fractures were the second most common pickleball injury (28.1%) reported (35). However, in the analysis by Weiss, upper-body injuries, such as to the wrist, were slightly more common than lower-body injuries (13.2%, 12.9%) (35).…”
Section: Pickleball Needs Analysissupporting
confidence: 61%
“…An injury analysis conducted by the authors yielded 4 recent references which discussed pickleball injuries (2,15,34,35). A case-report analysis of an older pickleball athlete (age 71 years) presented a unique hamstring injury coupled with a full-width tear of the left adductor magnus tendon at its ischial attachment (34).…”
Section: Pickleball Needs Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These competitive sports techniques can positively impact the overall comprehensive coordination ability of the participants' comprehensive strength, endurance, agility, speed skills, and balance skills [1][2] . In recent years, Chinese tennis has developed rapidly [3][4] . Tennis competitions have high requirements for male athletes' individual sports competencies, and technical movements are also fundamental, so the causes of tennis injuries are studied [5][6] .…”
Section: Introductionmentioning
confidence: 99%